2011
DOI: 10.1371/journal.pgen.1002266
|View full text |Cite
|
Sign up to set email alerts
|

Zelda Binding in the Early Drosophila melanogaster Embryo Marks Regions Subsequently Activated at the Maternal-to-Zygotic Transition

Abstract: The earliest stages of development in most metazoans are driven by maternally deposited proteins and mRNAs, with widespread transcriptional activation of the zygotic genome occurring hours after fertilization, at a period known as the maternal-to-zygotic transition (MZT). In Drosophila, the MZT is preceded by the transcription of a small number of genes that initiate sex determination, patterning, and other early developmental processes; and the zinc-finger protein Zelda (ZLD) plays a key role in their transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
574
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(626 citation statements)
references
References 40 publications
(94 reference statements)
37
574
1
4
Order By: Relevance
“…Vielfaltig is sufficient to activate enhancers that contain TAGteam motifs and required for early gene expression and cellularization (Liang et al 2008). While this work was under revision, it has further been shown that Vielfaltig binds to ;60% of all genomic instances of the TAGteam motif (Harrison et al 2011;Nien et al 2011). Our demonstration that Vielfaltig is a key determinant of early binding is intriguing and suggests that Vielfaltig might help to open (or keep open) chromatin and allow TFs to access their binding sites on DNA thereby defining early enhancers.…”
Section: Vielfaltig's Tagteam Motif Is a Key Regulator Of Early Tf Bimentioning
confidence: 92%
“…Vielfaltig is sufficient to activate enhancers that contain TAGteam motifs and required for early gene expression and cellularization (Liang et al 2008). While this work was under revision, it has further been shown that Vielfaltig binds to ;60% of all genomic instances of the TAGteam motif (Harrison et al 2011;Nien et al 2011). Our demonstration that Vielfaltig is a key determinant of early binding is intriguing and suggests that Vielfaltig might help to open (or keep open) chromatin and allow TFs to access their binding sites on DNA thereby defining early enhancers.…”
Section: Vielfaltig's Tagteam Motif Is a Key Regulator Of Early Tf Bimentioning
confidence: 92%
“…The maternal transcription factor Zelda (Zld; zinc finger early Drosophila activator) plays a primary role for the onset of zygotic genome activation in Drosophila embryos (Liang et al 2008;Nien et al 2011). Zld protein is present in nuclei considerably earlier than other key maternal transcription factors such as Bicoid (Bcd) and Dorsal (Dl) proteins and is bound to gene regulatory regions prior to zygotic genome activation (Harrison et al 2011;Nien et al 2011). Zld binding increases DNA accessibility and facilitates the binding of other transcription factors, including Bcd and Dl, to target enhancers (Foo et al 2014;Xu et al 2014 (Foo et al 2014).…”
Section: Pioneer Factors In Zygotic Genome Activationmentioning
confidence: 99%
“…Inducing zygotic genome activation Liang et al 2008 Increasing DNA accessibility in native chromatin Harrison et al 2011;Foo et al 2014;Xu et al 2014 Class V Pou (e.g., Oct3/4, Pou5f3) Zygotic genome activation (zebrafish/mouse) Inducing zygotic genome activation Foygel et al 2008;Lee et al 2013 Binding to target sites before zygotic genome activation Leichsenring et al 2013 Reprogramming from fibroblast to iPSCs (mouse/human) Inducing reprogramming Takahashi and Yamanaka 2006 Binding to chromatin that is not DNase-sensitive and not premarked by common histone modifications in vivo Soufi et al 2012 Group B1 Sox (e.g., Sox2) Zygotic genome activation (zebrafish/mouse) Inducing zygotic genome activation Pan and Schultz 2011;Lee et al 2013 Reprogramming from fibroblast to iPSCs (mouse/human) Inducing reprogramming Takahashi and Yamanaka 2006 Binding to chromatin that is nonhypersensitive and not premarked by common histone modifications in vivo Soufi et al 2012 Cancer progression (mouse/human) Inducing tumor formation Bass et al 2009;Boumahdi et al 2014 Klf4…”
Section: Updike and Mango 2006mentioning
confidence: 99%
“…Part of the answer involves transcription of Twine-degrading factors, 18 most likely regulated by Vielfältig/Zelda, the key transcriptional activator of the zygotic genome at the MBT. [20][21][22] In addition, precise control of timing is determined by the ability of the embryo to measure the ratio of nuclear content to the amount of cytoplasm (the nucleocytoplasmic ratio). At each cell cycle the amount of DNA doubles, and at a set number of cycles, which differs among organisms, the embryo senses through a still unclear mechanism that a correct ratio has been reached, and this initiates the degradation of Twine.…”
Section: The Midblastula Transition: Introducing Cell Cycle Complexitmentioning
confidence: 99%
“…5 Although a pre-MBT requirement for zygotic gene expression seems to be at odds with the concept that the zygotic genome is not transcribed before the MBT, recent evidence shows that Vielfältig/Zelda can surprisingly transcribe many genes prior to the MBT. 21,22,25 But why does Grapes/Chk1 cause pre-MBT degradation of String but not Twine? Mutation of the consensus Chk1 phosphorylation sites in Twine does not affect its stability, demonstrating that String and Twine are not regulated the same way.…”
Section: The Midblastula Transition: Introducing Cell Cycle Complexitmentioning
confidence: 99%